Pengaruh Model Jigsaw dalam Keterampilan Menulis Teks Pidato Siswa Kelas VIII - Ina Septiani; Hendra Setiawan; Roni Nugraha Syafroni (Universitas Muhammadiyah Surabaya, 2026)
The purpose of this study was to determine the extent of the ability of eighth grade students of SMP Negeri 2 Cikarang Pusat in writing speech texts using the jigsaw model. This study used a non-equivalent control group design, namely an experiment (quasi-experiment). The population of this study was all eighth grade students and the sample in this study was class VIII A as the experimental class and VIII B as the control class. Data processing using SPSS version 26 was carried out with normality, homogeneity, hypothesis, n-gain, and TCR tests. The results of this study were proven by the results of the tests given, namely the average posttest score for the ability to write speech texts using the jigsaw model was greater than the average pretest score before the application of the jigsaw model, the average pretest score was 59.33. After the puzzle model treatment was applied, the average posttest score was 85.33. And 88.13% was the result of the TCR. Based on these values, it can be concluded that the application of the jigsaw model is effective in improving the speech text writing skills of eighth grade students.